The length of the bridging chain in ansa-metallocenes influences their antiproliferative activity against triple negative breast cancer cells (TNBC). Issue 33 (8th June 2016) - Beauperin, Matthieu; Top, Siden; Richard, Marie-Aude; Plażuk, Damian; Pigeon, Pascal; Toma, Stefan; Poláčková, Viera; Jaouen, Gérard
Abstract : [ n ]Ferrocenophane and [ n ]ruthenocenophane derivatives have been synthesized and their antiproliferative activity evaluated against MDA-MB-231 cells. Abstract : In order to examine whether the length of the bridging chain in ansa-ferrocenes affects their antiproliferative activity against MDA-MB-231 triple negative breast cancer cell lines (TNBC), we synthesized derivatives of the type 1-[bis-(4-hydroxyphenyl)]methylidene-[ n ]ferrocenophane and 1-[(4-hydroxyphenyl)-phenyl]methylidene-[ n ]ferrocenophane with n = 3, 4, 5. We found that the derivatives of [3]ferrocenophane, the compounds with the shortest bridging chains, are the most active. IC50 values were 0.09 ± 0.01, 2.41 ± 0.10, and 1.85 ± 0.25 μM for the dihydroxyphenyl derivatives, with n = 3, 4, 5, respectively. These differences can be explained in terms of modification of the key metabolites (radical versus quinone methides) within the ansa series depending on the length of the bridging chain. The derivative of [5]ferrocenophane, possessing two –[bis-(4-hydroxyphenyl)]methylidene groups, was also prepared. Surprisingly, this relatively large molecule is also active (IC50 = 2.7 ± 0.3 μM). Two ruthenocenophane analogs were also synthesized. These ruthenium compounds are practically inactive against MDA-MB-231 cells. The unusual chemistry of these different compounds is discussed in terms of elucidating the mechanism underlying their diverse antiproliferative activity, and their specific advantages are evaluated.